BATAS-BATAS KONSTITUSIONAL HUKUM ISLAM DALAM HUKUM NASIONAL - muhamadun muhamadun; Murjazin Murjazin (JURNAL INDO-ISLAMIKA, 2018)
Indonesia is known as a country with a mixed legal system. The legal system currently in effect is dominated by three major legal systems, namely the Western legal system, the customary law system and the Islamic legal system. The basic rules that serve as guidelines and guidelines for citizens are extracted from the value system. This value system is expressed in the form of "collective agreement". This form of collective agreement is translated into the five basic principles of having a state, namely Pancasila. Within these limitations, there are gaps in applying Islamic teachings, which are limited to their substantive value. This study wants to explain why Islamic law cannot be used as the basis of the constitution and the extent to which the limitations are allowed in applying Islamic teachings as the teachings of the majority of Indonesian citizens. In responding to the issues surrounding the application of Islamic law in Indonesia, the discussion will focus on the concept of the constitution, sources of national law, and the form of the Muslim community's strategy in an effort to apply Islamic law within the national legal framework.